The impact of internal audit on enterprise risk management effectiveness in Jordanian public listed companies - Ahmad Jaber, Taha; Mohammed Shah, Sabarina; Johari, Jalila; Mustapha, Mazlina (HRMARS, 2024)
The study aims to investigate the level of the internal audit role in enterprise risk management and its impact on enterprise risk management effectiveness in Jordanian public-listed companies. Additionally, it aims to explore the impact of internal auditors' objectivity on enterprise risk management effectiveness and its potential moderating role in the relationship. The study employs a quantitative methodology through a cross-sectional survey. 119 questionnaires from 119 Jordanian public-listed companies were finally utilized for analysis using SPSS and SmartPLS software. The study results indicate that internal auditors are moderately involved in enterprise risk management roles, with participation rates of 60.71% in core roles, 53.14% in legitimate roles, and 24.57% in prohibited roles. Moreover, the results show that the internal audit role in enterprise risk management and internal auditors’ objectivity significantly positively impact enterprise risk management effectiveness. The results also reveal that internal auditors' objectivity does not moderate the relationship between internal audit role in enterprise risk management and enterprise risk management effectiveness. These results enhance knowledge and offer insights for practitioners and policymakers on the importance of the internal audit role in enterprise risk management and emphasize the crucial role of maintaining internal auditors' objectivity in enhancing overall enterprise risk management effectiveness.